ALIGNMENT ANALYSIS BETWEEN INDONESIA NATIONAL EXAMINATION AND CAMBRIDGE INTERNATIONAL EXAMINATION IN JUNIOR SECONDARY SCIENCE - Dzulfikar, Ahmad Fikri (2015)
Cambridge International Examination as benchmark International which follows 900 schools in over 160 countries. Indonesian students follows Cambridge International Examination to continue the study in others country. Then, Cambridge International Examination need to be a comparison of Indonesian National examination. This research is descriptive method by content analysis technique. Porter Alignment Index was used to measure alignment. Instruments that used for analysis are table analysis and matrix. The aims for this study are: (1) to analyze alignment in Science Indonesia National Examination and Cambridge International Examinational, (2) to analyze discrepancies by content, (3) to analyze discrepancies by cognitive process dimension, (4) to analyze discrepancies by knowledge dimension. Subject of research are Indonesia National Examination and Cambridge International Examination IGCSE level year 2013. The result of alignment index between Indonesia National examination and Cambridge international examination by knowledge dimension was laid on high level (0.8) and cognitive process dimension was laid on moderate level (0.6). The value of alignment is not 1, so there are discrepancies by content, cognitive process dimension and knowledge dimension. Ecosystem was over-represented in Indonesia National Examination three years, while matter over-represented in Cambridge International Examination three years. While, matter over-represented in Cambridge International Examination three years. The discrepancies by cognitive process dimension of remembering (C1), understanding (C2), and analyzing (C4) for almost all national examinations were under-represented in Indonesia National Examinations questions. While applying (C3) was over-represented in Indonesia National Examinations. But, in knowledge dimension the percentage fluctuates. Metacognitive dimension is not involved both of examinations.--------- Cambridge International Examination sebagai benchmark International yang diikuti oleh 900 sekolah dalam lebih dari 160 Negara. Pelajar Indonesia mengikuti Cambridge International Examination untuk melanjutkan sekolah mereka di Negara lain. Maka, Cambridge International Examination dibutuhkan untuk menjadi perbandingan oleh Ujian Nasional yang diselenggarakan di Indonesia. Penelitian ini adalah deskriptif yang menggunakan metode konten analisis tekhnik. Kesetaraan Index Porter (Porter Alignment Index) digunakan untuk mengukur nilai kesetaraan. Instrumen yang digunakan ialah tabel analisis dan matrix. Tujuan dari penelitian ini antara lain: (1) untuk menganalisis kesetaraan Ujian Nasional dan Cambridge International Examinational dalam pelajaran IPA, (2) untuk menganalisis perbedaan konten, (3) untuk menganalisis perbedaan level kognitif, (4) untuk menganalaisis perbedaan pada dimensi pengetahuan. Subjek dari penelitian ini ialah soal-soal Ujian Nasional Indonesia dan Cambridge International Examination IGCSE level tahun 2011-2013 pada pelajaran IPA. Hasilnya ialah nilai kesetaraan antara Ujian Nasional dan Cambridge international examination pada dimensi pengetahuan berada pada level tinngi (0.7) dan pada level kognitif termasuk dalam kategori sedang (0.6). Nilai kesetaraannya tidak 1, oleh sebab itu ada perbedaan pada konten, level kognitif, dan dimensi pengetahuan. Ecosystem lebih banyak terdapat pada soal Ujian Nasional dalam tiga tahun, sedangkan konten zat lebih banyak terdapat di soal Cambridge International Examination dalam tiga tahun. Perbedaan pada level kognitif Mengingat (C1), Memahami (C2), dan Menganalisis (C4) dari tiga tahun tidak banyak terdapat pada soal Ujian Nasional. Sedangkan Mengaplikasikan (C3) lebih banyak terdapat pada soal-soal Ujian Nasional. Akan tetapi, dalam dimensi pengetahuan presentasenya naik turun. Dimensi metakognitif tidak ada dalam soal-soal Ujian Nasional dan Camdbridge International Examination.